2002
DOI: 10.1073/pnas.072587199
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of NtcA-dependent promoters of Synechococcus sp. PCC 7942 by 2-oxoglutarate in vitro

Abstract: The transcription factor NtcA is a global regulator of nitrogen homeostasis in cyanobacteria. It thus positively regulates the expression of genes related to nitrogen assimilation such as glnA (which encodes glutamine synthetase) and ntcA itself in response to nitrogen shortage or depletion. The binding of NtcA to the glnA and ntcA promoters of Synechococcus sp. PCC 7942 in vitro now has been shown to be enhanced by 2-oxoglutarate. In vitro analysis of gene transcription also revealed that the interaction of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(143 citation statements)
references
References 33 publications
5
138
0
Order By: Relevance
“…The use of the glutamine synthetase inhibitor MSX indicated that metabolized (as opposed to ambient) ammonium suppressed the transcription of N genes in the Trichodesmium filaments, similar to our findings in marine Synechococcus (Lindell and Post, 2001;Lindell et al, 2005). This is consistent with the concept that a-oxoglutarate accumulates and acts as the NtcA activator molecule when ammonium supplies are limiting Tanigawa et al, 2002). NtcA-binding affinity to its DNA targets is enhanced by a-oxoglutarate (Vazquez-Bermudez et al, 2002).…”
Section: Ammonium Repressionsupporting
confidence: 80%
See 1 more Smart Citation
“…The use of the glutamine synthetase inhibitor MSX indicated that metabolized (as opposed to ambient) ammonium suppressed the transcription of N genes in the Trichodesmium filaments, similar to our findings in marine Synechococcus (Lindell and Post, 2001;Lindell et al, 2005). This is consistent with the concept that a-oxoglutarate accumulates and acts as the NtcA activator molecule when ammonium supplies are limiting Tanigawa et al, 2002). NtcA-binding affinity to its DNA targets is enhanced by a-oxoglutarate (Vazquez-Bermudez et al, 2002).…”
Section: Ammonium Repressionsupporting
confidence: 80%
“…However, enhanced transcription of napA overcame ammonium repression in the presence of the glutamine synthetase inhibitor MSX, consistent with NtcA regulation in Synechococcus spp. (Suzuki et al, 1993;Lindell and Post, 2001;Tanigawa et al, 2002;Lindell et al, 2005). Not all regulatory aspects of NtcA are known in diazotrophic cyanobacteria.…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…Crystal structures for the PII-PipX [15,16] Abbreviations: NtcA, nitrogen control factor of cyanobacteria; CRP, cAMP receptor protein, also called CAP, catabolite gene activator protein; PipX, PIIinteracting protein X; SYCRP1, Synechocystis CRP; 2OG, 2-oxoglutarate; RU, relative unit; SPR, surface plasmon resonance; FC1 and FC2, flow cells 1 and 2, respectively of the Biacore chip; IPTG, isopropyl-b-D-thiogalactoside only binds to PII if MgATP also binds), three PipX molecules are sequestered by one PII trimer in such a way that they become unavailable for activating NtcA. 2OG activates NtcA-dependent gene expression regulation [10,11] and also triggers (when ATP is also bound) the release of PipX from PII [13], making PipX available for coactivation of NtcA. The structures of NtcA bound to 2OG alone [15,17] or together with PipX [15] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…While CRP is activated by cAMP [5,8,9], NtcA is activated by 2-oxoglutatare (2OG) [10,11], an indicator of the cellular nitrogen level [12], and it is coactivated by a small (10 kDa) monomeric protein called PII-interacting protein X (PipX) [13,14] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…During nitrogen deprivation, binding of NtcA to its own promoter leads to an enhanced transcription of ntcA. In addition to being autoregulated at the level of gene expression, transcriptional regulation exerted by NtcA is modulated in response to the C-to-N balance of the cells and 2-oxoglutarate has been shown to exert a positive effect on NtcA function both in vivo and in vitro (Tanigawa et al, 2002;Valladares et al, 2008;Va´zquez-Bermu´dez et al, 2003). 2-Oxoglutarate is the substrate of GOGAT and thus the acceptor molecule for fixed nitrogen.…”
Section: Early Events and Pattern Formationmentioning
confidence: 99%